Divergent Jewish cultures : Israel and America - Moore, Deborah Dash, 1946-; Troen, S. Ilan (Selwyn Ilan), 1940- (Studies in Jewish culture and society., 2001)
Two creative centres of Jewish life rose to prominence in the twentieth century, one in Israel and the other in the United States. Although Israeli and American Jews share kinship and history drawn from their Eastern European roots, they have developed divergent cultures from their common origins, often seeming more like distant cousins than close relatives. Using examples from literature, art, history, and politics, this book explores why this is so, examining how two communities that constitute eighty per cent of the world's Jewish population have created separate identities and cultures.